2000
DOI: 10.1038/81677
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy, the most common cause of glomerulonephritis, is linked to 6q22–23

Abstract: End-stage renal disease (ESRD) is a major public health problem, affecting 1 in 1,000 individuals and with an annual death rate of 20% despite dialysis treatment. IgA nephropathy (IgAN) is the most common form of glomerulonephritis, a principal cause of ESRD worldwide; it affects up to 1.3% of the population and its pathogenesis is unknown. Kidneys of people with IgAN show deposits of IgA-containing immune complexes with proliferation of the glomerular mesangium (Fig. 1). Typical clinical features include onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(194 citation statements)
references
References 22 publications
(14 reference statements)
3
182
0
6
Order By: Relevance
“…Many LGWS and GWAS in both familial and sporadic IgAN suggest that there is a strong genetic component in the disease. [7][8][9][10][11][12] However, most studies have not evaluated the contribution to this complex disorder of other forms of genetic variation, such as structural variations, mainly in the form of CNVs. 15 Indeed, CNVs have recently been shown to have an important role in complex disease phenotypes as psoriasis, 30 rheumatoid arthritis 31 and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many LGWS and GWAS in both familial and sporadic IgAN suggest that there is a strong genetic component in the disease. [7][8][9][10][11][12] However, most studies have not evaluated the contribution to this complex disorder of other forms of genetic variation, such as structural variations, mainly in the form of CNVs. 15 Indeed, CNVs have recently been shown to have an important role in complex disease phenotypes as psoriasis, 30 rheumatoid arthritis 31 and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…)del overlapped with the region named IGAN1 identified in a GWLS. 7 The aberrations chr17. ?)dup, containing ankyrinrepeat and fibronectin type III domain gene, overlapped with the region found in linkage in our previous GWLS.…”
Section: Identification Of Concordant Aberrations In Igan Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association studies identified distinct loci on chromosomes 6p21, 8p23, 17p13, 22q12, 1q32. 6,7 On the other hand, classical linkage studies performed on AD families identified additional loci on chromosomes 2q36, 4q26-31, 6q22, 17q12-22, [8][9][10] lending further support to the complex etiology and broad genetic heterogeneity of the disease.…”
Section: Introductionmentioning
confidence: 90%
“…although genetic linkage analyses (5) and association studies (6)(7)(8) have implicated several loci and candidate genes in the predisposition to cKd, the genes that confer susceptibility to this condition remain to be identified definitively. In addition, given ethnic differences in lifestyle and environmental factors as well as in genetic background and renal function, it is necessary to examine genetic variants related to cKd in each ethnic group.…”
Section: Introductionmentioning
confidence: 99%